Arrhythmogenic KCNE gene variants: current knowledge and future challenges - Crump, Shawn M.; Abbott, Geoffrey W. (Frontiers in Genetics, 2014)
There are twenty-five known inherited cardiac arrhythmia susceptibility genes, all of which encode either ion channel pore-forming subunits or proteins that regulate aspects of ion channel biology such as function, trafficking and localization. The human KCNE gene family comprises five potassium channel regulatory subunits, sequence variants in each of which are associated with cardiac arrhythmias. KCNE gene products exhibit promiscuous partnering and in some cases ubiquitous expression, hampering efforts to unequivocally correlate each gene to specific native potassium currents. Likewise, deducing the molecular etiology of cardiac arrhythmias in individuals harboring rare KCNE gene variants, or more common KCNE polymorphisms, can be challenging. In this review we provide an update on putative arrhythmia-causing KCNE gene variants, and discuss current thinking and future challenges in the study of molecular mechanisms of KCNE-associated cardiac rhythm disturbances.